Development and Implementation of the Military Treatment Facility Engagement Committee (MTFEC) to Support Pragmatic Clinical Trials in the Military Health System. (25th January 2021) - Scarton, Dylan V; Roddy, William T; Taylor, Jerika A; Geda, Mary; Brandt, Cynthia A; Peduzzi, Peter; Kerns, Robert D; Pasquina, Paul F
ABSTRACT: Introduction: Within the population of military service members and veterans, chronic pain is highly prevalent, often complex, and frequently related to traumatic experiences that are more likely to occur to members of this demographic, such as individuals with traumatic brain injury or limb loss. In September 2017, the National Institutes of Health (NIH), Department of Defense (DOD), and Department of Veterans Affairs (VA) Pain Management Collaboratory (PMC) was formed as a significant and innovative inter-government agency partnership to support a multicomponent research initiative focusing on nonpharmacological approaches for pain management addressing the needs of service members, their dependents, and veterans. Methods: A Pain Management Collaboratory Coordinating Center (PMC3) was also established to facilitate collective learning across 11 individually funded pragmatic clinical trials (PCTs) designed to optimize the impact of the PMC as an integrated whole. Although the DOD and VA health care systems are ideal sites for the enactment of PCTs, executing these trials within the local context of DOD military treatment facilities (MTFs) can present unique challenges. The Military Treatment Facility Engagement Committee (MTFEC) was created to support the efforts of the PMC3 in its role as a national resource for development and refinement of innovative tools, best practices, and other resources in the conduct of high impact PCTs. Results: The MTFEC is composed of experts from each service who bring experiences in executing clinical pain management trials that can enhance the planning and execution of the PCTs. It provides expertise and leadership in the execution of research studies at within MTFs and within the DOD health care system, with guidance from PMC3 Directors and in collaboration with NIH, DOD, and VA program and scientific officers. Discussion/Conclusion: Considering the importance of enacting large-scale, pragmatic studies to implement effective strategies in clinical practice for chronic pain management, the MTFEC has begun to actualize its purpose by identifying potential barriers and challenges to study implementation and exploring how the PMC can support and aid in the execution of PCTs by applying similar approaches to stakeholder and subject matter engagement for their research.